دراسة العلاقة بين جودة الخدمة ورضا العملاء دراسة ميدانية على المشافي الخاصة في مدينة اللاذقية - قاسم, سامر; علي, سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims to analyze the reality of the health service in the Syrian private hospitals in Lattakia City; by answering the following questions:* What is the level of the health service in hospitals in terms of the availability of the following basic dimensions: Tangibility, empathy, responsiveness, assurance and security, reliability and credibility?* What is the impact of the dimensions of health service quality in customer satisfaction?The survey form was designed and distributed to (105) customer of the patients who checked in private hospitals in Lattakia City, where a convenience sample was chosen.The results of research indicated, that there is a good understanding of the following dimensions: Tangibility, empathy, responsiveness, and assurance and security between members of the research sample. The study results also indicated that there is a significant and positive effect of (empathy and emphasize security and reliability) dimensions on customer satisfaction as dependent variable, which the regression model explained (80%) of the differences in customer satisfaction, while Tangibility and speed of response did not affect customer satisfaction as a dependent variable.يهدف البحث إلى تحليل واقع الخدمة الصحية في المشافي السورية الخاصة في مدينة اللاذقية؛ وذلك بالإجابة على التساؤلات الآتية: * ما هو مستوى الخدمة الصحية في المشافي من حيث توفر الأبعاد الأساسية وهي : الملموسية، والتعاطف، وسرعة الاستجابة،و التأكيد والضمان،و الموثوقية والمصداقية؟* ما هو أثر أبعاد جودة الخدمة الصحية على رضا العملاء؟تم تصميم استمارة استبيان وُزِع على (105) زبون من المرضى الذين ارتادوا المشافي الخاصة في مدينة اللاذقية، و تم اختيارها بطريقة العينة الميّسرة،. أشارت نتائج البحث إلى أنه يوجد إدراك جيد لمحور الملموسية بين أفراد عينة البحث، وكذلك لمحور التعاطف، وسرعة الاستجابة، والتأكيد والضمان، وإدراك متوسط لمحور الموثوقية والمصداقية, وكذلك لرضا العميل بين أفراد عينة البحث. كما أشارت الدراسة إلى وجود أثر ايجابي ذي دلالة معنوية لكل من (التعاطف والتأكيد والضمان والموثوقية) في رضا العميل بوصفه متغيرا تابعا، إذ وضح نموذج الانحدار (80%) من الاختلافات في رضا العميل، بينما لم تؤثر الملموسية وسرعة الاستجابة في رضا العميل متغيرا تابعا.